2013
DOI: 10.1083/jcb.201304031
|View full text |Cite
|
Sign up to set email alerts
|

Augmin-dependent microtubule nucleation at microtubule walls in the spindle

Abstract: Electron tomography and 3D modeling identifies augmin-dependent connections between the wall of one microtubule and the minus end of a neighboring one in the spindle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(123 citation statements)
references
References 40 publications
5
118
0
Order By: Relevance
“…However, unlike other cases, the branch angle utilized in this cell type was highly variable. Branching nucleation with a fixed angle has been thought to be an excellent cellular approach to not only amplify MT numbers, but also polarize the MT network (Janson et al, 2005;Murata et al, 2005;Kamasaki et al, 2013;Petry et al, 2013). Our observation suggests that protonemal cells utilize this mode of MT nucleation simply to increase MT numbers.…”
Section: Mechanism Of Branching Nucleationmentioning
confidence: 57%
See 1 more Smart Citation
“…However, unlike other cases, the branch angle utilized in this cell type was highly variable. Branching nucleation with a fixed angle has been thought to be an excellent cellular approach to not only amplify MT numbers, but also polarize the MT network (Janson et al, 2005;Murata et al, 2005;Kamasaki et al, 2013;Petry et al, 2013). Our observation suggests that protonemal cells utilize this mode of MT nucleation simply to increase MT numbers.…”
Section: Mechanism Of Branching Nucleationmentioning
confidence: 57%
“…In this mechanism, a conserved eight-subunit complex, augmin, binds to spindle/ phragmoplast MTs, recruits the g-tubulin ring complex (g-TuRC), and thereby nucleates new MTs. Studies in animal systems have shown that daughter MTs are nucleated predominantly at <20°a ngles from mother MTs during this process, indicating that this mechanism is suitable for generating the parallel MT arrays commonly seen in the spindle and phragmoplast (Kamasaki et al, 2013;Petry et al, 2013). A recent report has shown that augmin also plays a role in MT-dependent MT nucleation by recruiting the g-TuRC in the cortical MT arrays (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Such a nucleation pattern is now recognized to be shared by animal cells and recapitulated by electron microscopy [14,23]. The augmin complex interacts with the gTuRC and likely recruits the latter to MT walls to initiate branching nucleation with shallow angles (<30 ); such a nucleation event has been reconstituted in vitro using frog egg extracts [24].…”
Section: Augmin Is Specifically Associated With Mt-dependent Mt Nuclementioning
confidence: 96%
“…Existing microtubules for example trigger nucleation of new microtubules through augmin-mediated recruitment of microtubule nucleation complexes leading to local microtubule amplification (Clausen and Ribbeck 2007;Petry et al 2013). Directionally biased microtubule-dependent nucleation can reinforce an existing polarity (Smertenko et al 2011;Kamasaki et al 2013). Another example of feedback involves the dynamic instability of microtubules in bundles, which is adapted locally through recruitment of CLASP or KIF4 by bundling proteins (Bratman and Chang 2007;Bieling et al 2010).…”
Section: Discussionmentioning
confidence: 99%